Identifikasi Tingkat Pengetahuan, Sikap, dan Perilaku PHBS Warga Kelurahan Pasir Mulya, Kecamatan Bogor Barat - Dimas Athar Zaydan; Nanda Amirah Luthfiyah; Andini Rizky Awalia; Ilham Huda Ramadhan; Rizkia Putri Maulina Sihombing (Journal of Applied Psychology and Health Studies, 2025)
Public health problems in Indonesia are a challenge that requires serious attention from the government and the community itself. This study aims to analyze the relationship between the knowledge and attitude of the community in Kelurahan Pasir Mulya towards Clean and Healthy Living Behavior (PHBS). The research method involved a survey with 30 respondents carefully selected to represent the population in Kelurahan Pasir Mulya. Data was collected through interviews, written questionnaires, and direct observation with Likert and Guttman scale methods and analysis of the results. The results showed that although some of the community members have attitudes that support the implementation of PHBS, their knowledge is still limited especially related to the indicators of healthy latrines and smoking. Efforts are needed to increase awareness of the importance of maintaining cleanliness and health in the household environment. These findings emphasize the need for community education and empowerment in implementing PHBS to create a healthier environment and support community welfare. Therefore, further socialization and education are needed to support enthusiastic community attitudes regarding the implementation of PHBS to improve the quality of life and health of the community in Kelurahan Pasir Mulya. This research makes an important contribution in understanding the factors that influence community PHBS behavior and provides a basis for the development of more effective and sustainable public health programs.